PENERAPAN PERAWATAN SPA KAKI UNTUK MENINGKATKAN PERFUSI PERIFER PADA PASIEN DIABETES MELITUS TIPE 2 DI RSUD Dr. (H.C) Ir. SOEKARNO - ADELIA RAHMADIANY; Abdul Kadir Hasan; Dudella Desnani Firman Yasin (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Diabetes mellitus type 2 is one of the non-communicable diseases that can be caused by unhealthy living habits and diet that cause hyperglycemia, this is due to the body's lack of insulin both absolute and relative so that blood viscosity increases and impacts ineffective peripheral perfusion.Type 2 diabetes mellitus is one of the non-communicable diseases that can be caused by unhealthy living habits and diet that cause hyperglycemia, this is due to the body's lack of insulin both absolute and relative so that blood viscosity increases and impacts ineffective peripheral perfusion. Foot spa therapy is one of the nursing interventions that can be done to prevent ineffective peripheral perfusion and other complications in the feet. Case study objective is to describe foot spa therapy in patients with type 2 diabetes mellitus with ineffective peripheral perfusion nursing problems. The design of this scientific paper is descriptive with a case study research approach by applying nursing interventions based on evidence of practice. This case study data collection method uses participatory observation, structured interviews, documentation, literature study. The results of the case study show that the application of foot spa therapy for five days can improve peripheral perfusion so that blood flow is smooth and prevent the occurrence of ineffective peripheral perfusion. The conclusion obtained is that the application of foot spa therapy in type 2 Diabetes Mellitus patients with ineffective peripheral perfusion problems can be prevented so that based on the article it is proven that the application of foot spa therapy is effective to be applied as a prevention of ineffective peripheral perfusion.